Government Regulation of the Food Sector: Factor-Targeted Approach - NAKIPOVA, Gulmira; BAKYT, Kalykova; ALMAGUL, Cheirkhanova; NURGUL, Maulina; MAIRA, Omarova (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The article examines the approaches of representatives of various economic schools in solving problems of state regulation of the food sector. The author, highlighting the major conceptual differences are scientific positions, substantiates the necessity of application in the management of the industry factor and target-oriented approach.